Chlorination roasting of the cathode material contained in spent lithium-ion batteries to recover lithium, manganese, nickel and cobalt. (January 2022) - Barrios, Oriana C.; González, Yarivith C.; Barbosa, Lucía I.; Orosco, Pablo
Graphical abstract: Highlights: Chlorination roasting with Cl2 was proposed to recover value metals from spent LiBs. Lithium, manganese, nickel and cobalt start to react with Cl2 at different temperatures. The metals from the spent cathode material were recovered as chlorides. The action of Cl2 is direct without intervention of another reagent. The optimal conditions of the chlorination reaction were 900 °C and 90 min. Abstract: Chlorination roasting was examined as an alternative method to recover lithium, manganese, nickel and cobalt as chlorides from the cathode material of spent lithium-ion batteries. The roastings were performed using chlorine as chlorinating agent. The effect of temperature and reaction time on the recovery of the metals was investigated performing non-isothermal and isothermal roasting assays. The non-isothermal roasting was studied from room temperature to 900 °C and the isothermal roastings were studied at temperature of 400 to 900 °C and reaction periods from 0 to 90 min. The experimental results showed that metals start to react with chlorine at different temperatures: lithium at 400 °C; manganese and nickel at 500 °C and cobalt at 600 °C. The extraction yield of all metals increased markedly with the increase in temperature. The roasting of the cathode material with chlorine at 900 °C for 90 min produced an extraction yield of 100% for all metals.